Hydrodynamic modes of holographic Weyl semimetals - Nishal Rai; Karl Landsteiner (Physics Letters B)
We study the quasinormal modes of a holographic model of a Weyl semimetal. The model features quantum phase transition between a topological phase and a trivial phase. We put particular emphasis on the hydrodynamic modes and show that a hydrodynamic mode is present only in the topological Weyl semimetal phase.